• 1) sin(alpha-beta)+cosalpha sinbeta=sinalpha cosbeta-sinbeta cosalpha+cosalpha sinbeta =sinalpha cosbeta;

    2) frac{cos(frac{pi}{2}-t)*ctg(-t)}{sin(frac{pi}{2}+t)}=frac{sint*ctg(-t)}{cost}=tgt*-(ctgt)=-1;

    3) ctg(-t)*sint+cos(pi+t)=-frac{cost}{sint}*sint-cost =-cost-cost=-2cost.

  • 1) sin(a-b)+cos a*sin b =sina*cosb — cosa*sin b+cos a*sin b=sin a*cos b

    2)cos(пи/2 — t)*ctg(-t)/sin (пи/2+t) = — sin t *ctg t/cos t =(-sint*cost/sint)/cost =

    = -cost/cost = -1

    3)ctg(-t)*sin t +cos(пи + t)=-cost/sint*sin t -cost =-cost-cost=-2cost